UPAYA GURU MENINGKATKAN HASIL BELAJAR SISWA MELALUI MOTIVASI - Istiyanti, Istiyanti (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2009)
To improve the student learning outcomes, the role of teachers in providing the motivation necessary for the motivation of student learning outcomes can be improved. Learning can not be achieved effectively and efficiently without being accompanied by motivation. The more appropriate given the motivation to learn that the better results obtained. Teachers' efforts to motivate students in learning, among others provide learning facilities such as libraries, discipline and so forth. While the efforts made by teachers to motivate students in learning outside of school as an independent study at home, form study groups and the allocation of time to learn, so students can learn in regular patterns.